Ecological consequences of non-native fish invasion in Eastern Cape headwater streams - Ellender, Bruce Robert (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
The introduction, spread and concomitant impacts of non-native species are a global problem. Fish are among the most widely introduced vertebrate groups, with their impacts affecting multiple levels of organisation- from individuals, populations and communities, to entire ecosystems. In South Africa, the largest perceived threat to range-restricted endemic headwater stream fishes is said to be invasion by non-native fishes, however, as is the case elsewhere, invasive impacts are often a case of risk perception rather than actual risk analysis. Two range-restricted headwater species, the Eastern Cape redfin Pseudobarbus afer and the Border barb Barbus trevelyani are redlisted by the International Union for the Conservation of Nature (IUCN) as 'Endangered', primarily due to invasion by non-native fishes. To investigate invasions in South Africa, and provide a quantitative estimate of the impact of non-native fishes on the two imperilled endemics, P. afer and B. trevelyani, the overall aims of this thesis were to: (A) Provide a literature review on non-native fish invasions in South Africa; (B) Using two case studies on the headwaters of the perennial Keiskamma and episodic Swartkops River systems, investigate the naturalisation-invasion continuum to provide a holistic view of the invasion process in these variable environments. The specific thesis objectives were: (1) Reviewing current knowledge of invasive impacts of non-native fishes in South Africa; (2) Investigating invasibility of headwater stream environments by non-native fishes; (3) Determining the establishment success of non-native fishes, (4) Assessing the spatial and temporal impacts of invasion; (5) Understanding mechanisms responsible for non-native fish impacts; (6) Investigating the threat of non-native fish invasion on the genetic diversity of two the two headwater fishes, P. afer and B. trevelyani. Results from the literature review of fish invasions (Chapter 1) showed that South Africa has a long history of non-native fish introductions, spanning two and a half centuries. Currently, 55 species have been introduced or translocated. Many of these introduced species have become fully invasive (36%). Their impacts also span multiple levels of biological organisation. There was a general paucity of studies on fish invasions (38 studies), however, of those conducted, reviewed studies placed emphases on invasive impacts (25 studies) and the transport, introduction, establishment and spread stages of the invasion process were largely ignored. The two study systems, the Swartkops and Keiskamma Rivers, were heavily invaded and numbers of introduced species surpassed that of natives (Chapter 2, 3 and 5). Headwater streams had varying invasibility and a number of non-native species were successfully established (Chapter 2, 3, 5 and 6). The remainder of the invasions were casual incursions into headwater streams from source populations in mainstream and impoundment environments which were invasion hotspots. Irrespective of establishment, four predatory invaders (largemouth bass Micropterus salmoides, smallmouth bass M. dolomieu, brown trout Salmo trutta and rainbow trout Oncorhynchus mykiss) impacted heavily on native fish communities (Chapter 3, 4 and 5). Two broad types of invasion were documented, top down invasion by non-native O. mykiss and S. trutta and upstream invasion by M. salmoides and M. dolomieu (Chapter 3 and 5). Their impacts included changes in community structure, extirpation from invaded stream reaches resulting in contracted distribution, and isolation and fragmentation of native fish populations. The impacts of non-native predatory fishes were particularly acute for P. afer and B. trevelyani. Where non-native predatory fish occurred, P. afer and B. trevelyani had been extirpated (Chapter 3 and 5). As a result both native species exhibited contracted distributions (>20% habitat loss due to invasion). Upstream invasion by centrarchids isolated and fragmented P. afer populations into headwater refugia, while top down invasion by salmonids excluded B. trevelyani from invaded, more pristine stream reaches, by forcing the species into degraded unsuitable lower stream reaches. Predation also disrupted population processes such as adult dispersal for P. afer, and centrarchid-invaded zones acted as demographic sinks, where adults dispersing through invaded reaches were rapidly depleted. While the Mandela lineage of P. afer exhibited little within or between drainage genetic structuring, B. trevelyani was >4% divergent between drainages, and up to 2% divergent between streams within the Keiskamma River system (Chapter 7). The distribution of genetic diversity for B. trevelyani also indicated that the loss of diversity was imminent without immediate conservation interventions. This thesis has provided conclusive evidence that native fishes are vulnerable to invasion and that non-native predatory fishes have significant impacts on native fishes in Eastern Cape headwater streams. If management and conservation measures are implemented, the unwanted introduction and spread of non-native fishes may be restricted, allowing native fishes opportunities for recovery.
Keywords: Fishery management -- South Africa -- Eastern Cape; Fishes -- Conservation -- South Africa; Introduced fishes -- South Africa -- Eastern Cape; Introduced organisms